Nepotism, illegitimacy and papal protection in the construction of a career: Rodrigo Pires de Oliveira, Bishop of Lamego (1311-1330†) - Saraiva,Anísio Miguel de Sousa (2008)
Dom Rodrigo de Oliveira was one of many fourteenth-century Portuguese clergymen who reached the top of the ecclesiastical hierarchy as a result of the widespread practice of nepotism. The social fabric that catapulted this cleric into the religious hierarchy and the subsequent development of his cursus honorum reflect an era in which kinship and protectionism were essential for a career in the clergy. As the illegitimate son of the influential Archbishop of Braga, Dom Martinho Pires de Oliveira (1296-1313), Dom Rodrigo benefited from the support of the archbishop (who favored his relations and dependants as part of a far-reaching strategy), and from the indispensable protection of Popes Boniface VIII and Clement V, thanks to the archbishop’s prominence and influence at the Papal Court. Dom Rodrigo de Oliveira’s career began in the chapter of Évora (a city where his paternal family were influential) before he had attained the regulation age of fourteen. From there, he moved on to become prior of the important collegiate church of Santa Maria de Guimarães, then Dean of Évora, and soon afterwards, Bishop of Lamego, a position he received by pontifical appointment after having failed to be elected to the office of Bishop of Évora. Thus, it was in this context that the profile of Dom Rodrigo was constructed, supported mainly by a strategy of favor dictated by family interests, and benefiting widely from papal protection through the successive concession of prerogatives of privilege and exception.